The association of ultra-processed food intake with mental health disorders, cognitive impairment, and insomnia: a literature review - Lenart, Julia; Janik, Natalia; Górowska, Anna; Wadowska, Zuzanna; Janowiak, Julia; Sobiś, Martyna; Bogacka, Anna; Kiersznowska, Nina; Buchman, Małgorzata; Miłek, Barbara (Quality in Sport, 2025)
Background Ultra-processed foods like packaged snacks, instant meals, desserts, and sweetened beverages have become dominant in the modern diet and are now under investigation for their potentially harmful impact on human health. Aim This article aims to present current knowledge of the relationship between ultra-processed food consumption and the risk of mental health disorders, cognitive impairment and insomnia. Material and methods A literature review was conducted across PubMed and Google Scholar. Keywords included: ultra-processed foods, mental health, depression, anxiety, cognitive function, cognitive performance, cognitive impairment, insomnia. Results Multiple studies showed significant connection between high ultra-processed food consumption and elevated risk of mental health disorders such as depression and anxiety. Increased risk of dementia and Alzheimer’s disease among adult population was also reported. Moreover, the reviewed studies showed that ultra-processed foods negatively affect sleep and may contribute to insomnia, particularly among adolescents. Conclusions High ultra-processed food consumption has multiple adverse health outcomes and harmfully affects human mental health, cognitive functions and sleep. Public health strategies and dietary guidelines that include the avoidance of overall ultra-processed food intake are needed to improve population health. Given the popularity of ultra-processed products, this issue should be addressed by public health organizations without further delay. Further research is required to confirm this association and to clarify its complexities.